Manganese biogeochemistry in the Southern Ocean, from Tasmania to Antarctica. Issue 6 (24th April 2021) - Latour, Pauline; Wuttig, Kathrin; van der Merwe, Pier; Strzepek, Robert F.; Gault‐Ringold, Melanie; Townsend, Ashley T.; Holmes, Thomas M.; Corkill, Matthew; Bowie, Andrew R.
Abstract: Manganese (Mn) is an abundant element in the Earth's crust. However, its concentrations in open ocean seawater are low, where external inputs are scarce. In this study, we report the dissolved Mn and particulate Mn distributions in the Southern Ocean, measured along the GEOTRACES—SR3 transect, from Tasmania (Australia) to Antarctica in the Southern Ocean, during the austral summer 2018. Both dissolved Mn and particulate Mn concentrations were generally low away from localized sources (< 0.3 nmol L −1 and < 0.1 nmol L −1, respectively) along the transect. Our observations of a lower labile particulate fraction than previously measured suggest the Southern Ocean has a unique particulate Mn composition. Low surface dissolved Mn concentrations were attributed to biological uptake and few external sources. Our results suggest biological control of the Mn cycle was higher above the Antarctic continental slope, compared to the rest of the section, and our particulate Mn : P ratios indicated the presence of iron‐stressed diatoms south of the Sub‐Antarctic Front. We suggest low dissolved Mn surface concentrations may (co‐)limit phytoplankton growth in this region. Localized higher dissolved Mn concentrations were observed due to external sources, such as sedimentary and hydrothermal inputs. The presence of an eddy at the same latitude as a hydrothermal plume induced an upwelling of hydrothermally enriched waters up to 1000 m; however, no dissolved Mn inputs to the surface waters were observed. We suggest previous dissolved Mn inputs to the surface layer may be obscured by biological uptake.